2007
DOI: 10.1002/ppul.20696
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in cGMP, soluble guanylate cyclase, phosphodiesterase 5, and B‐type natriuretic peptide induced by chronic increased pulmonary blood flow in lambs

Abstract: Alterations in sGC subunit protein expression during the first post-natal month, and increased BNP levels during the second post-natal month contribute to elevations in plasma and lung tissue cGMP in lambs with increased pulmonary blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Lambs with increased PBF have increased levels of cGMP, unlike the GW9662-treated lambs. This increase is mediated via stimulation of particulate guanylate cyclase activity by BNP [30] and despite increased PDE5 activity [31]. We did not find changes in PDE5 activity with GW9662-treatment alone.…”
Section: Discussionmentioning
confidence: 69%
“…Lambs with increased PBF have increased levels of cGMP, unlike the GW9662-treated lambs. This increase is mediated via stimulation of particulate guanylate cyclase activity by BNP [30] and despite increased PDE5 activity [31]. We did not find changes in PDE5 activity with GW9662-treatment alone.…”
Section: Discussionmentioning
confidence: 69%
“…25 In experimental animals, increased pulmonary blood flow and associated pulmonary hypertension are accompanied by raised circulating levels of BNP and cGMP. 26 The levels of these 2 factors also were closely correlated in patients with Eisenmenger syndrome, potentially obscuring any direct association between NO and cGMP production. Increased circulating inflammatory mediators also accompanied raised plasma NO x levels, and cytokine-inducible NO synthase (NOS) expression has been described in pulmonary arteries and cardiac tissues of patients with flow-associated pulmonary hypertension and cyanotic congenital heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of PDE5 has been observed in rat models of mesenteric occlusion where functional studies suggested that it attenuates increased NO signaling (Zhang et al, 2009). PDE5 is also induced in heart and lung in response to chronic pressure overload (Oishi et al, 2007; Vandenwijngaert et al, 2013), and in resistance pulmonary arteries to hyperoxia (Farrow et al, 2008), and underscores the complex changes in gene expression that determine signaling through the NO/cGMP signaling pathway. To the best of our knowledge PDE5 inhibitor drugs have not been tested for salutary effects on coronary blood flow in this model of chronic coronary occlusion.…”
Section: Discussionmentioning
confidence: 98%